Humanisme Bagi Sesama – Menyingkap Akar Kekerasan Dalam Relasi Antarmanusia Dan Etika Tanggung Jawab Menurut Emmanuel Levinas - Editha Soebagiyo (Seri Filsafat Teologi, 2020)
This article contains the most fundamental text of Emmanuel Levinas. His unique contribution is his argument that the morality is not a branch of philosophy, but first philosophy (TI 304). His starting point is the actual concrete encounter, with the “face” of the other, that underlies our sense of self and identity, and this, in turn is the beginning of Levinas’ understanding of what Philosophy is. Philosophy begins with the other and ethics is undertood as a relation of infinite responsibility to the other person. By this, he means that when we face someone, before we decide to respond others (to wish someone “great day”, to give or not to give money to a beggar), we are already put into a relationship with them. This is the reason why he calls that relationship ‘the original relation’. This unconditional responsibility is not something we take on or a rule by which we agree to be bound, it exists before us and we are ‘thrown’ into inexhaustible responsibility for them without any choice. Although his big idea is not adequate for the solution of all our ethical problems, we find the strength of Levinas’ position in reminding us to the nature of ethical demand, which must be presupposed at the basis of all moral theories.